An analysis of anomalously wet summers in the South Western Cape of South Africa - De Kock, Wade Matthew (Department of Oceanography, 2023)
Unlike the rest of South Africa, the southwestern Cape (SWC) experiences most its rainfall in the austral winter (May-September). Due to interannual, intraseasonal and interdecadal variability, drought is a familiar occurrence. The SWC recently suffered from an extended dry period, known as the ‘Day Zero Drought' during 2015-2018, where greater Cape Town nearly ran out of piped water supply. Despite most rainfall in the SWC occurring from MaySeptember, considerable rainfall events have been known to occur during the summer (October-March). Such events could play a substantial role in mitigating winter droughts and multiyear droughts the region suffers from. Large Rainfall Events (LREs) during the summer of 2018/19 caused average dam levels in all major dams of the SWC to increase by more than 1%. The dam level increase is significant during the driest period of the year where dam levels decrease by several % per month. This study investigates all LREs during the summer (October-March) from 1979-2019 and their effects on major dam levels. Most summer LREs are found to be linked to atmospheric rivers (ARs) or cut-off lows (COLs), which together account for up to 88% of the top 75 LREs. Apart from one study characterising the considerable effect of ARs on winter rainfall, to date little research on ARs has been done for the region. Furthermore, COLs have been suggested to occur mostly during transition seasons. This thesis reveals that although ARs last shorter than COLs and lead to a smaller area receiving rainfall in the SWC, they both yield intense rainfall amounts with ARs concentrated around Greater Cape Town. After LREs have occurred, average dam volumes were shown to increase by up to 5% making LREs essential in drought recovery. Anomalously wet summers, which typically contain more LREs than average, are also mostly associated with cooler temperatures and less extreme hot days (90% decile). Rainfall totals are inversely correlated (r=-0.44) with extreme hot days. In addition, extreme hot days also show a significant increasing trend of 2.8 days/decade from 1979-2019. Along with increased cloud cover, weaker winds over dam catchment areas can be associated with 4 out the 5 wettest summer seasons. Of the 5 wettest summer seasons, only one (2013/14) occurred in the last two decades. Anomalously cool and wet summers, reduce the water consumption impact on dam volumes as well as help reduce the impacts of drier than normal winter seasons. Wet and cool summer seasons also reduce fire risk in the region which is important considering that the region is agriculturally productive and has experienced several devastating fires in recent decades, both in agricultural areas as well as in greater Cape Town. Although the extended summer contributes only about 30% of the year's annual rainfall, summer LREs occur during the most water demanding part of the year. Notably, increased summer LREs usually correspond with anomalously wet summers. This thesis finds that anomalously wet summers can be characterized by increased rainfall days which are linked to increased cyclonic anomalies over the region and westerly moisture fluxes shifted anomalously equatorward in the South Atlantic. These changes in circulation patterns are found to be linked to a negative Southern Annular Mode pattern and in the late summer, also linked to ENSO and the zonal wave number 3 pattern. Overall, trends suggest decreases in rainfall days in the Greater Cape Town region and in the nearby mountain areas where most major dams are located for the mid to late summer (December-March). These decreases in rainfall days can be related to poleward expansions of the South Atlantic High Pressure (SAHP) which then lead to decreases in storms impacting the SWC. With storm tracks occurring further poleward due to moisture corridor shifts and SAHP poleward expansions during recent years, there is a decrease in summer LREs in the SWC. Some of these poleward shifts are related to the tendency of the Southern Annular Mode to be in positive phase in recent decades. Since summer LREs are important in mitigating droughts in the region, future work needs to consider rainfall in all seasons rather than just the historical focus on winter rainfall which has been relatively well studied. This thesis shows the potential importance of anomalously wet summers as essential contributors to moisture in the region during the driest period of the year.